A dose‐escalation clinical trial of intranasal ketamine for uncontrolled cancer‐related pain. Issue 4 (21st February 2022) - Singh, Vinita; Gillespie, Theresa W.; Lane, Olabisi; Spektor, Boris; Zarrabi, Ali John; Egan, Katherine; Curseen, Kimberly; Tsvetkova, Maya; Beumer, Jan H.; Sniecinski, Roman; Shteamer, Jack W.; Switchenko, Jeffery; et al.
Abstract: Study Objective: The objective of our study was to determine safety and pharmacology (pharmacokinetics and preliminary efficacy) of intranasal (IN) ketamine for uncontrolled cancer‐related pain. Design: Dose escalation clinical trial. Setting: Outpatient. Patients: Ten adult patients with uncontrolled cancer‐related pain. Intervention: Each patient received escalating doses of ketamine over four visits, each 2–5 days apart: 10 mg IN at visit 1, 10 mg intravenous (IV) at visit 2, 30 mg IN at visit 3, and 50 mg IN at visit 4. Measurements: Pain was measured before and after drug administration for up to 4 h using the 11 point (0–10) Numerical Pain Rating Scale (NPRS). Main Results: All subjects had advanced cancer, with intractable pain, despite being on moderate dosage of opioids. There was a statistically significant reduction in median NPRS by 1.5 (1–4), 3 (2–3), and 4 (3–5) points at 60 min after receiving the medication and remained decreased by 1.5 (1–2), 2 (1–2) and 1 (1–4) points at the end of the study visit (240 min) with the 10 mg, 30 mg and 50 mg IN dosage, respectively. The median percentage of maximal pain relief being 22.5 (16.6–71.5), 65.5 (40–100), and 69.25 (50–100) for 10 mg, 30 mg and 50 mg IN dosage, respectively and 100 (75–100) with 10 mg IV dose. All side effects (nausea and feeling of unreality) resolved by the end of each study visit. No severe adverse events occurred. Conclusion: In this single‐institution study, all dosages of IN ketamine administered in the study (10, 30, and 50 mg) provided significant pain relief for intractable cancer‐related pain and were well tolerated. The 50 mg dose provided maximal pain relief without major side effects. Further study focused on repeated administration efficacy and safety for cancer‐related pain is warranted.